Luxified Troglodytism? Mapping the subterranean geographies of plutocratic London. Issue 3 (September 2019) - Baldwin, Sophie; Holroyd, Elizabeth; Burrows, Roger
Abstract : The history of London has long been entwined with expansions of financial capital and the machinations of global plutocrats and their more proximate counterparts. 1 However, what has happened in the decade since the global financial crisis is without precedent. London has been transformed into a city for global capital rather than one designed to meet the needs and aspirations of the majority of its denizens. 2